Somatic mutation landscape reveals differential variability of cell-of-origin for primary liver cancer. Issue 2 (February 2020) - Ha, Kyungsik; Fujita, Masashi; Karlić, Rosa; Yang, Sungmin; Xue, Ruidong; Zhang, Chong; Bai, Fan; Zhang, Ning; Hoshida, Yujin; Polak, Paz; Nakagawa, Hidewaki; Kim, Hong-Gee; et al.
Abstract: Primary liver tissue cancer types are renowned to display a consistent increase in global disease burden and mortality, thus needing more effective diagnostics and treatments. Yet, integrative research efforts to identify cell-of-origin for these cancers by utilizing human specimen data were poorly established. To this end, we analyzed previously published whole-genome sequencing data for 384 tumor and progenitor tissues along with 423 publicly available normal tissue epigenomic features and single cell RNA-seq data from human livers to assess correlation patterns and extended this information to conduct in-silico prediction of the cell-of-origin for primary liver cancer subtypes. Despite mixed histological features, the cell-of-origin for mixed hepatocellular carcinoma/intrahepatic cholangiocarcinoma subtype was predominantly predicted to be hepatocytic origin. Individual sample-level predictions also revealed hepatocytes as one of the major predicted cell-of-origin for intrahepatic cholangiocarcinoma, thus implying trans-differentiation process during cancer progression. Additional analyses on the whole genome sequencing data of hepatic progenitor cells suggest these cells may not be a direct cell-of-origin for liver cancers. These results provide novel insights on the nature and potential contributors of cell-of-origins for primary liver cancers. Abstract : Systems biology; Biocomputational method; Gene mutation; Genomics; Cancer research; Bioinformatics-based prediction of cell-of-origin; Primary liver cancers; Integration of epigenome, Genome and single-cell RNA-Seq data.